Study of Role of Voluntary Agencies in the Implementation of Social Welfare Programmes - Planning Commission (Planning Commission, 1970)
The papers on methodology, objectives, scope, sampling design guide points, schedules & questionnaires and instructions thereon have been got together of Compendium for the convenience of the Officers engaged on the study. The papers have been finalized on the basis of the seminar held for the purpose which was attended by the Regional Evaluation Officers in addition to the Senior Officers of the PEO at the Headquarters and the representatives of the concerned Divisions in the Planning Commission. The comments received from the Department of Social Welfare, Central Social Welfare Board and the Social Welfare Division of the Planning Commission, have also been suitably incorporated.
Design, Schedules, Etc., and Instructions Programme Evaluation Organisation Planning Commission Government of India